BAT-BORNE ZOONOTIC VIRUS: A LITERATURE REVIEW - Agustina, Kadek Karang (Buletin Veteriner Udayana, 2024)
Bats are flying mammals that are known to be reservoirs of many diseases, especially viruses. Several dangerous and zoonotic viruses are transmitted by bats. This paper aims to provide a systematic summary of zoonotic viruses that can be transmitted by bats. This paper uses the PRISMA method. The review showed that some important viral diseases transmitted to humans by bats are Ebola, Nipah, SARS-CoV, MERS-CoV, Hendra and Rabies. The case fatality rate caused by these diseases is very high to above 50% of the sufferers. It can be concluded that vigilance must continue and be increased against bats that can threaten human and animal health at any time. Understanding and judiciously managing interactions between humans and bats is critical to the prevention of zoonotic diseases.